TANTANGAN DAN STRATEGI MANAJEMEN KEUANGAN PADA UMKM CV BIDWI KARYA - Rani Rifania Nursyafa; Heriyanto Heriyanto (Yayasan Insani Mandiri Santani, 2025)
This research aims to analyze the challenges and formulate a financial management strategy in CV. Bidwi Karya uses a SWOT analysis approach. CV. Bidwi Karya still faces obstacles in financial management, especially due to the use of manual recording methods which are at high risk of errors and delays in reports. SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats that a company faces. The results of the study show that CV. Bidwi Karya has a fairly systematic recording system and a clear team structure as a strength, but still has weaknesses in terms of technology and recording efficiency. Opportunities that can be leveraged include the adoption of modern accounting software and improving team competencies, while threats that need to be anticipated are industry competition and regulatory changes. Based on these findings, several strategies were formulated such as digitization of the financial system, human resource training, and cooperation with financial consultants. This strategy is expected to be able to increase the efficiency, accuracy, and resilience of CV financial management. Bidwi Karya in facing internal and external challenges. Keywords: financial management, strategy, digitalization